Simbolizem v otrokovem pripovedovanju zgodbe in skrivnostnost ugank - Gorinšek, Manja (Otrok in knjiga, 2013)
Children's stories are children's own portraits; growing up, child is acquiring experience of his environment; he also forms his own picture and learns to convey the things he is competent for. His narration is affected by a number of factors, the first and foremost being upbringing in the closest family, followed by parent's education, kindergarten attendance, frequency of reading, library visits, etc.
Keywords: pripovedovanje; zgodbe; uganke; child; otroci